Sistem Pengatur Irigasi Sawah Menggunakan Metode Irigasi Alternate Wetting and Drying Berbasis Teknologi Internet of Things - Tisnainil Husna; Dody Ichwana; Werman Kasoep (Universitas Andalas, 2018)
Rice is the staple food of the majority of Indonesians and most of the population work as farmers. However, the amount of rice produced are still insufficient. To meet the rice needs for the society, it should increase the amount of rice production by focusing on rice field quality such as the water level rice fields. In this study a prototype rice field irrigation system is designed using AWD irrigation method by regulating open activation and closing the inlet gate and exit gate based on the age of paddy which are calculated using RTC and the height of paddy water measured using ultrasonic sensors. The system also designed to receive input from the age of paddy and deactivate the system from the mobile application through the ESP8266 module. Test results from this system can measure water level with accuracy of 95.68% and read real-time time with 98.67% accuracy. The servo motor NFC DS04 works to open the door with a duration of 60 seconds and closes the door with a duration of 56 seconds. The paddy irrigation regulating system can regulate the water level with a success percentage of 81.48%. The system can receive input and deactivate the system with a percentage of success of 70%.